Herbal formula (Danggui Beimu Kushen Wan) for prostate disorders: a systematic review of classical literature - Hong Li; Andrew Hung; Angela Wei Hong Yang (Integrative Medicine Research)
Background: Danggui Beimu Kushen Wan (DBKW) was initially known for difficult urination in pregnancy and has been widely used for prostate disorders in modern days. This study aimed to comprehensively investigate the implications of DBKW in traditional evidence. Methods: The Encyclopedia of Traditional Chinese Medicine was searched to identify the ingredients, dosage, etiologies, pathogeneses, actions and indications related to DBKW documented in ancient books. Descriptive summary was provided to their characteristics. Results: A total of 41 texts in 36 classic books were included. Two etiologies and 10 pathogeneses were investigated. All the identified formulas contain Angelicae Sinensis Radix, Fritillariae Thunbergii Bulbus and Sophorae Flavescentis Radix with the ratio of 1:1:1. The treatment dosage is three to 10 pills each time. The primary indication of DBKW is difficult urination with heat stagnation. Nine included texts specified that this formula could also be used for male. Conclusion: Included classic literature has provided fundamental evidence for the management of difficult urination in female and male. Further studies should investigate its mechanisms of actions for difficult urination related conditions, such as prostate disorders. Keywords: Herbal medicine, Prostate disorder, Urination, Classic literature, Text mining.